Experiments in participatory econometrics: improving the connection between economic analysis and the real world - Rao, Vijayendra (2002)
What the author calls ` participatory econometrics' provides a way for economists to respond better to the challenge of the real world. To illustrate the approach, an example, is outlined of a research project that used participatory econometrics to understand the behaviour of poor households. Some generalisations on the added value of participatory econometrics over more conventional methods of analysis are then briefly drawn. - Reproduced.
Keywords: Econometrics